KARAKTERISTIK MAKANAN PENDAMPING ASI INSTAN LOKAL MENGGUNAKAN CAMPURAN TEPUNG BERAS MERAH DAN TEPUNG DAUN KELOR (Moring olifera) - Zakaria Zakaria; Ramlan Asbar; Sukmawati Sukmawati; Sarmila Sarmila (Media Gizi Pangan, 2019)
One of the causes of malnutrition in children is a habitual pattern of complementary feeding of breast milk is inappropriate, the ignorance about the ways of feeding in infants and the low quantity and quality of the complementary food that given to children. The purpose of the research is to find out the characteristics of quality of chemical (nutrient), physical, acceptability of complementary food by using local uses instant Brown rice flour and moringa leaf flour. The research method is postest only,  formulations namely F1 (75: 5), F2 (72.5: 7.5), F3 (70:10), and F4 (67, 5: 12,5) to supply per 100 g of ingredients and complete the nutritional content using full cream powder 15 g and sugar 5 g. The nutrient content of the raw material of brown rice and moringa leaf flour was analyzed proximate in the laboratory, full cream milk powder and sugar using the nutrient composition of the literature source. The best product analysis uses the De Garmo effectiveness method. The results showed that formula of complementary food with the best local Instant value 0.59, namely Formula 1 with consecutive energy nutrient 393.2 kcal, protein 9.3 g, fat 9.4 g, carbohydrate 56.3 g, fiber 16.33 g, moisture content 5.4%, grey levels 8.5%.Characteristics of the physical density of kamba 0.5 g/ml and water absorption 1 ml/g. Physical characteristics based on the density of 0.5 g / ml and water absorption 1 ml / g. The power to receive the best formula based on aspects of color, aroma, texture, taste is received (liked) by the panellists